2018
DOI: 10.1016/j.msard.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Adverse psychiatric effects of disease-modifying therapies in multiple Sclerosis: A systematic review

Abstract: The DMTs reviewed were not associated with an increased risk of adverse psychiatric effect in MS, and some may reduce the incidence of depressive symptoms. This may reflect either a positive direct effect (e.g. immune modulation) or an indirect effect arising due to a positive impact on disease activity or course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 82 publications
0
21
0
Order By: Relevance
“…In clinical trials, anxiety has been observed as a rare ADR to the combination product nicotinic acid and laropiprant 22 . However, no increased risk of psychiatric ADRs has been identified for dimethyl fumarate 23 . Therefore, further research seems warranted.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In clinical trials, anxiety has been observed as a rare ADR to the combination product nicotinic acid and laropiprant 22 . However, no increased risk of psychiatric ADRs has been identified for dimethyl fumarate 23 . Therefore, further research seems warranted.…”
Section: Discussionmentioning
confidence: 97%
“…22 However, no increased risk of psychiatric ADRs has been identified for dimethyl fumarate. 23 Therefore, further research seems warranted. HCA 2 is present in microglial cells of all brain areas and might mediate neuroprotective effects of dimethyl fumarate in patients with MS. 3,24 As glial cells are involved in the pathogenesis of anxiety disorders, 25 Increased liver enzymes were identified as similarly distributed to dimethyl fumarate and nicotinic acid in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding treatment of MS depression, immunomodulatory and immunosuppressive drugs, namely disease modifying therapies (DMTs), such as oral dimethyl fumarate, teriflunomide, fingolimod, and intravenous drugs, such as natalizumab, and alemtuzumab (Kirzinger et al, 2013;Hunter et al, 2016;Montanari et al, 2016;Gasim et al, 2018) seem to modulate depressive symptoms in MS. Furthermore, some of these DMT drugs exert a direct beneficial effect on glutamatergic and GABAergic synaptic transmission by modulating inflammatory mediators (Gentile et al, 2016(Gentile et al, , 2018Mandolesi et al, 2017).…”
Section: Clinical Insights For Cytokine Theorymentioning
confidence: 99%
“…If 36–54% of PwMS are confronted with anxiety and studies have clearly shown that anxiety (and depression) is also associated with cognitive impairment,90 therapy counseling “in an open and honest partnership” with our PwMS is a conditio sine qua non 91. The questionable association between “depression” and “DMT therapy” was investigated by Gasim et al (side effects of DMT with regard to psychiatric comorbidities in natalizumab, dimethylfumarate, teriflunomide and alemtuzumab) 92. DMTs have not been associated with an increased risk of adverse psychiatric effects and some may even reduce the incidence of depressive symptoms.…”
Section: Maximizing Therapeutic Opportunities To Delay the Transitionmentioning
confidence: 99%
“…DMTs have not been associated with an increased risk of adverse psychiatric effects and some may even reduce the incidence of depressive symptoms. This may reflect either a positive direct effect of immune modulation or an indirect effect resulting from a positive influence on disease activity or course 92. PwMS with progressive course of MS also showed an increase in pain and disability 93.…”
Section: Maximizing Therapeutic Opportunities To Delay the Transitionmentioning
confidence: 99%